Optimalisasi Fitur TikTok dan Implikasinya pada Personal Branding - Herlianti Marta, Nofaria; Erdiansyah, Rezi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Social media makes it easy for some people to share personal matters and activities. One of the social media used for personal branding is TikTok. The most widely used platform among internet users worldwide is TikTok. This his TikTok app offers a variety of features such as visual and audio effects, easy editing tools, filters, etc.that help individuals enhance their personal branding through her TikTok. The authors investigated this because she wanted to see if using Tikok features could further enhance personal branding, and also the impact of using TikTok features on improving personal branding. This is because she wanted to measure, this study uses Peter Montoya's eight laws of personal branding theory. Thisastudy usedaa quantitativeaapproach using Google Forms surveyymethod among his 100 respondents. IBM SPSS 22astatistical softwareewas usedafor dataaanalysis. Thearesearch resultsaobtained through testing withhAnova atta significanceelevel of00.000 demonstrate theeimpact of TikTok feature optimization on improving personal branding. Media sosial memberikan kemudahan bagi sebagian orang untuk berbagi urusan dan aktivitas pribadi. TikTok merupakannsalah satuemedia sosiallyang digunakannuntuk personallbranding. Platform yang paling banyak digunakan dikalangan pengguna internet seluruh dunia adalah TikTok. Aplikasi TikTok ini menawarkan berbagai fitur seperti efek visual dan audio, alat pengeditan yang mudah, filter, dan lainnya membantu individu meningkatkan personal branding mereka melalui TikTok. Penulis melakukan penelitian ini karena ingin mengetahui apakah penggunaan fitur-fitur TikTok dapat lebih meningkatkan personal branding dan bagaimana penggunaan fitur-fitur TikTok mempengaruhi peningkatan personal branding. Karena penulis ingin mengukurnya, penelitianiiniimenggunakan teoriieight lawspersonalbbranding dari PetermMontoya. Penelitianiini menggunakanspendekatan kuantitatif denganametode survei Google Forms dengan jumlah responden sebanyak 100 orang. Perangkat lunak statistik IBM SPSS 22 digunakanauntuk analisissdata. Hasilapenelitianayang diperolehhmelalui pengujian Anova denganatingkat signifikansio0,.000 menunjukkannadanya pengaruhhoptimasi fitur TikTok terhadap peningkatan personal branding.